Influence of the use of Co-Substrates on the anaerobic Co-Digestion of municipal solid waste, cocoa industry waste and bottled beverage industry waste (2023)
Colombia generates large quantities of organic waste that are not used or deposited in the correct way. Therefore, this project seeks to harness the organic load of these residues using anaerobic co-digestion, which is a biological process that allows the recovery and the biochemical potential of methane (BPM) from waste, thus, achieving adequate treatment for the control of environmental pollution. In this project, three residues were evaluated: Municipal solid waste (MSW), cocoa industry waste (CIW) and bottled beverage industry waste (BBIW). To these residues, a physical-chemical characterization was realized prior to the BMP test, in which the following was determined: values of solid volatile particles, total solids, organic matter and nitrogen Kjeldahl. With the characterization obtained, we prepared the mixtures in which the carbon nitrogen (C/N) ratio was varied in three levels: 25, 35 and 45. The number of grams of volatile solids (gVS) was also varied in three levels: 0.5, 1.25 and 2. Likewise, the co-substrate was varied in two: sewage sludge and pig manure. It was found that mixtures having a C/N of 35 grams of volatile solids of 0.5 and using as co-substrate the pig manure generate a greater production of methane (364 mLCH4/gSV). The anaerobic co-digestion technique allows the efficient development of the process due to the synergistic behavior of the co-substrates used, which compensate for the shortcomings that each presents when performing the process separately. It is also important to mention that the mixtures that have cocoa industry waste and bottled beverage industry waste increase the biochemical potential of methane. Although this may change when the bottled beverage industry waste is replaced with the municipal solid waste since the composition is the same. Copyright © 2018, AIDIC Servizi S.r.l.